Immunofluorescence evidence of cryptosporidium in water - Zainutdin, Fatin Khairunnisa; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (2016)
Cryptosporidium causes cryptosporidiosis which can cause serious health effects especially to immunocompromised people. While this parasite can spread in several ways, transmission through ingestion of infected water is the most common way. Many studies have been conducted in several countries pertaining to the occurrence of Cryptosporidium in water sources including Malaysia. However, the information and data collected for the occurrence of Cryptosporidium in river water, especially in state of Pahang is still insufficient. Hence, the study aimed to determine the occurrence of Cryptosporidium oocysts in two main rivers in Kuantan. Water samples were collected and processed immediately after each sample collection. Cryptosporidium oocysts were isolated by using immunomagnetic separation technique and were stained using FITC-belled anti-crypto sp monoclonal antibody stain and observed under immunofluorescence microscope. The result showed that all water samples were positive with Cryptosporidium oocysts. The oocysts were stained in fluorescence green and appear to be in spherical shape ranging from 4-6µm in size under immunofluorescence microscope. Shedding of infected faeces from humans or animals into the river is believed to be a major contributor to the occurrence of Cryptosporidium oocysts in water. The findings can provide useful information regarding the occurrence of Cryptosporidium oocysts in water.